Menjaga Autentisitas Bacaan al-Quran melalui Tashil di Pesantren al-Hikmah Purwosari Kediri - Roni Susanto; Muhamad Afif Ulin Nuhaa (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
This research discusses the problem of authenticity in the qur’an. This authenticity problem is proven by the decline in the quality of students' reading of the qur’an. The decline in quality refers to 2 things, namely the accuracy of the letters and the properties of the letters. This problem certainly needs to be followed up to maintain the authenticity of the reading of the Koran, which is in accordance with the demands. This research uses qualitative methods with analysis in the form of content analysis with three stages, namely data condensation, data display and conclusions. This research aims to discuss the Tashil program in maintaining the authenticity of Al-Qur'an reading located at PP al-Hikmah Purwoasri Kediri. This research provides a new contribution in maintaining the authenticity of Al-Qur'an reading in Tahfidz Islamic boarding schools in the form of tashil learning.